2018
DOI: 10.1007/s00253-018-8801-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection and cell sorting of Pseudonocardia species by fluorescence in situ hybridization and flow cytometry using 16S rRNA-targeted oligonucleotide probes

Abstract: Pseudonocardia spp. are receiving increasing attention due to their ability to biodegrade recalcitrant cyclic ether pollutants (e.g., 1,4-dioxane and tetrahydrofuran), as well as for their distinctive ecological niches (e.g., symbiosis with ants/plants and production of antibiotics). Isolating and characterizing Pseudonocardia spp. is thus important to discern their metabolic and physiological idiosyncrasies and advance their potential applications. However, slow growth, low cell yield, and dissimilar colony m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…For example, in a study by Yamamoto et al (2018), medium pH was 7.0–7.3, and incubation was performed at 28℃ while shaking at 120 rpm. Besides, Mengyan et al reported that their conditions for growing Gram‐positive bacteria included fixation of washed cells in 1 ml of ethanol/phosphate‐buffered saline (PBS) (1:1, v/v) and incubation at room temperature for 2 h. Also, for Gram‐negative bacteria, resuspension was done in 1 ml of 4% paraformaldehyde and fixation was performed at 4℃ for 3 h. After fixation, all cells were washed twice with 500 μl of 1X PBS and stored at −20℃ (Li, Yang, et al, 2018). In a study by Shan et al, the isolation media were supplemented with 20 μg/ml of nystatin to suppress the fungal growth.…”
Section: Isolation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a study by Yamamoto et al (2018), medium pH was 7.0–7.3, and incubation was performed at 28℃ while shaking at 120 rpm. Besides, Mengyan et al reported that their conditions for growing Gram‐positive bacteria included fixation of washed cells in 1 ml of ethanol/phosphate‐buffered saline (PBS) (1:1, v/v) and incubation at room temperature for 2 h. Also, for Gram‐negative bacteria, resuspension was done in 1 ml of 4% paraformaldehyde and fixation was performed at 4℃ for 3 h. After fixation, all cells were washed twice with 500 μl of 1X PBS and stored at −20℃ (Li, Yang, et al, 2018). In a study by Shan et al, the isolation media were supplemented with 20 μg/ml of nystatin to suppress the fungal growth.…”
Section: Isolation Methodsmentioning
confidence: 99%
“…After fixation, all cells were washed twice with 500 μL of 1 X PBS and stored at -20°C (Li et al 2018b). In a study by Shan et al, the isolation media were supplemented with 20 g/mL of nystatin to suppress the fungal growth.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Because of its extreme hydrophilicity and chemical stability, dioxane is resistant to conventional physical–chemical treatments . Though a plethora of dioxane-metabolizing microbes are available, their application for in situ bioremediation has been greatly stymied by the facts that (1) trace levels of dioxane (parts per billion) in the field are insufficient to sustain the growth of the amended metabolizers or stimulate the expression of responsible enzymes, (2) most isolates are Gram-positive filamentous Actinomycetes (Figure A) that are inclined to form clumps (Figure S1) that presumably prevent efficient subsurface distribution, and (3) co-occurring chlorinated compounds, especially 1,1-DCE, inhibit or even cease the removal of dioxane by archetypic dioxane degraders (e.g., Pseudonocardia dioxanivorans CB1190). , In addition, 1,1-DCE is also a recalcitrant compound partially because of the cellular toxicity derived from its biotransformation metabolite, 1,1-DCE epoxide. , Given the high coexistence frequency and persistence of dioxane and 1,1-DCE, the development of an effective remediation approach to synchronize the removal of both contaminants is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in parallel with the findings of bacterial strains capable of degrading 1,4-dioxane in different environments over the last two decades [3,[15][16][17], previous studies have assessed the feasibility of several bioremediation strategies to treat 1,4-dioxane-contaminated groundwater, including natural attenuation, biostimulation, and bioaugmentation. The occurrence of natural attenuation, which depends on the intrinsic degrading abilities of indigenous microorganisms, has been verified in lab-scale microcosm studies [18][19][20] and in field surveys [21,22], indicating monitored natural attenuation as a potential remedial strategy.…”
Section: Introductionmentioning
confidence: 99%